Understanding the Relationship between Humans, Culture, and Civilization in Islamic - Devika Amanda Dahlia Putri (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2024)
Abstract This research aims to explore the relationship between humans, culture, and civilization through literary studies. This study is based on the necessity to gain a comprehensive understanding of how these three entities interact across various social and historical contexts. By collecting and analyzing various sources such as books, journal articles, and other relevant materials, this study aims to provide a deeper understanding of the dynamics of this relationship. Literary analysis reveals the defining role of culture as a shaper of human identity and the social structure of civilization. The research findings also highlight the impact of globalization, technology, and socio-political changes on the relationship between these three entities. Emphasis on the importance of a deeper understanding of the dynamics of human interaction, culture, and civilization to respond to the challenges and opportunities in building a sustainable future for humanity. The importance of this understanding is attributed to the progression in time and changes occurring globally. Together, this study highlights the complexity of the relationships between people, culture, and civilization, and the importance of understanding their dynamics to create a broader understanding of human development as a whole. Thus, this study makes an important contribution to the development of a more comprehensive perspective on the interaction between these three entities in human society. Together, this study highlights the complexity of the relationships between people, culture, and civilization, and highlights the importance of understanding their dynamics to create a broader understanding of human development as a whole. Keywords: Civilization, Culture, and Human